The Role of CSR as a Moderating Variable in Optimizing The Performance of The Halal Cosmetics Industry - Warno Warno (KEUNIS, 2026)
This quantitative study examines the effects of management, internal control systems (ICS), and QRIS-based digital payments on the performance of MSMEs operating in the Indonesian halal cosmetics industry, involving Corporate Social Responsibility (CSR) as a moderating variable. Data were collected using the survey technique from 300 halal cosmetics MSMEs across various regions in Indonesia and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that management has a significant positive effect on MSME performance, ICS has no direct effect on MSME performance, while QRIS adoption has a significant negative effect on MSME performance. CSR significantly strengthens the relationship between ICS and MSME performance, but it does not moderate the effects of management or QRIS on MSME performance.